Performance Analysis of Twelve Lead ECG Based on Delivery Distance Using Bluetooth Communication - Azel Pralingga Mukti; Lusiana Lusiana; Dyah Titisari; Satheeshkumar Palanisamy (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
Based on data from Basic Health Research (Riskesdas) in 2018, the incidence of heart and blood vessel disease is increasing from year to year. At least 15 out of 1000 people or about 2,784,064 individuals in Indonesia suffer from heart disease. Therefore, cardiovascular health care can make a better diagnosis through continuous monitoring. The purpose of this study was to develop a 12-lead circuit, a lead selector (Wilson Central Terminal), an instrumentation booster, an analog filter (Notch Filter 50Hz), Arduino UNO, a Bluetooth module, and Delphi7 application to display electrocardiograph signals. The results show that the Bluetooth module cannot send a signal at a distance of 20 meters if there is no obstacle, cannot send a signal at a distance of 10 meters if there is an obstacle in the form of a wall, and cannot send a signal at a distance of 16 meters if there is an obstacle in the form of wood (doors).